Genomic and proteomic characterisation of primary colorectal tumours in the Malaysian population / Lau Tze Pheng - Lau, Tze Pheng (2014)
Colorectal cancer (CRC) is a multifactorial disease whereby gene-gene and gene-environment interactions contribute to its development and progression. It is also polygenic in nature, hence a large number of genetic alterations, each conferring a small genotypic risk, determine the individual’s susceptibility to this disease. Therefore, it is of clinical importance to identify potential CRC susceptibility gene candidates for improvement of future CRC screening and surveillance. This can be achieved by screening low-penetrant genetic variants via case-control studies across populations worldwide. Here, we investigated the association between several genetic variants and CRC susceptibility, i.e., the NOD2, XRCC1, EGF and VEGF genes, as well as the top-ranked GWAS-identified CRC-associated common variants. The genotyping of these genetic variants was performed via Real-Time PCR with TaqMan chemistry. Rs4939827 was the only common variant associated with CRC susceptibility with regards to our local population. We also attempted to characterise the CRC tumour-specific mRNA and proteomic profiles in our samples as both mRNA and protein expression patterns are more dynamic compared to the genetic codes. Hence, to investigate the differential gene expression in the primary CRC tumours, we used a two-step ACP-based PCR approach which was then followed by a confirmatory test with RT-qPCR. We successfully characterised distinctive gene expression signatures for both early- and advanced stage CRC tumours. The under-expression of ARPC2, together with the over-expression of RPL35, RPS23 and TIMP1, are the main features of early stage CRC tumours. In contrast, the advanced stage CRC group is characterised by the over-expression of C6orf173, RPL35, RPS23 and TIMP1. After performing comparison protein expression analysis using a combination of 2-D DIGE and LC-MS/MS platform, we identified 10 significantly over-expressed and 6 significantly under-expressed proteins in the Stage II CRC neoplasms, but none was reported for either Stage III or IV CRC tumours. For decades, CRC has been a constant threat to the well-being of the human population notwithstanding the fact that it can be treated if detected at an early stage. With the latest advances in the therapeutic management of metastatic CRC through the screening for KRAS mutation, we hope our findings may complement current CRC management efforts in the search of potential molecular markers for diagnostic, prognostic and treatment response predictive purposes.